Space Law and Space Mining, Exploring New Horizons Amid COVID-19 Pandemic - Marcin Jakub Drobnik; Ivan Bimbilovski; Shubham Pathak (Emerging Science Journal, 2023)
This study analyses the current scenario with COVID-19 affecting the international and Thai space law, and its impacts and corresponding repercussions upon the Thai economy, ASEAN region and then at international level. The methodology adopted for this study is a mixed method with qualitative research tools collected from key informant interviews and focus group discussions. The data analysis involves the Strength, Weakness, Opportunity, and Threat (SWOT) analysis, which has been integrated with Hierarchical Thematic areas to provide the supporting model for wholesome recommendations through analyzing the findings from the research. The key respondents involved several government officials associated with Thai space agencies and departments, along with judges, lawyers, researchers, academicians, non-government organizations (NGO) officials, and law students. The findings provided the need for adoption of Treaty leading to the creation of a space organization which would be accountable towards setting up a legal framework for commencement of space mining operations. The international space tribunal is to be created under this international space organization to resolve any disputes arising out of space mining. The overall implications of this research would lead to the sharing of the benefits of space mining with both developed and developing countries to enhance sustainable development for all mankind. Doi: 10.28991/ESJ-2023-SPER-09 Full Text: PDF